Two General Algorithms for Computing Fixed Points of Nonexpansive Mappings in Banach Spaces - Shuang Wang (Journal of Applied Mathematics)
Recently, Yao et al. (2011) introduced two algorithms for solving a system of nonlinear variational inequalities. In this paper, we consider two general algorithms and obtain the extension results for computing fixed points of nonexpansive mappings in Banach spaces. Moreover, the fixed points solve the same system of nonlinear variational inequalities.